Petition for writ of mandamus in the Special Court - dos Santos Madela, Taina (Seven Editora, 2023)
The law currently understood as the set of norms and customs created to monitor and regulate social relations, as society develops, seeks to submit its operators to new forms of provision of its services whenever a legal provision changes. In Special Courts, in general, interlocutory decisions cannot be appealed, so there is a wide range of decisions on which there is no provision for an immediate appeal, and this would, in principle, give rise to a greater margin of applicability of a writ of mandamus. However, as the decisions of the Courts do not go to the respective Court of Justice (TJ), Federal Regional Courts (TRF), or Superior Court of Justice (STJ), these have few instances of standardization of understanding. Well, there is TNU, but it sometimes unifies decisions against the STJ. Law 9,099/95 does not have any provision regarding the appeal, which is not against the sentence, such as, for example, the innominate appeal. However, with the advent of the laws of the Federal Court and the Court of the Treasury, provisional protection was provided in the Special Court, with this provision these laws allowed an appeal against the provisional guardianship decision, which is also an innominate appeal, however, follows the logic of an instrument grievance. The Federal Supreme Court (STF), when defining the topic 77 of general repercussion in 2009, decided that a writ of mandamus is not applicable for interlocutory decisions issued in the cases submitted to the Courts, and these decisions will be challenged when the innominate appeal is filed against the sentence. Lay judges base their decisions based on art. 38 of Law 9,099/95, which provides for the organization of courts, meeting the principles relevant to art. 2 of the same law, celerity, simplicity, orality, procedural economy. For this reason, the present work intends as a general objective to understand the filing of a writ of mandamus in special courts, and as a specific objective, to clarify the express reasoning behind the decisions. Methodologically, the work approaches a literature review, of a qualitative nature, and uses the technical procedures of bibliographic research, using research in books, articles, websites, and abstracts. DOI: 10.56238/pacfdnsv1-071